Shifting Concept of Balance of Administrative Responsibility Between Users and Construction Service Providers - Nurliana Ritonga; Triono Eddy; Onny Medaline (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The principle of equality, as stipulated in Article 2 of Law Number 2 of 2017 concerning Construction Services, requires a balanced position between construction service users and service providers in fulfilling rights, obligations, and risk allocation. However, in practice, this principle often remains normative and is not fully implemented in construction contracts in Indonesia. This study aims to analyze the shifting concept of administrative responsibility between service users and construction service providers, as well as its implications for legal certainty and justice in construction projects. This research employs a normative juridical method with statutory and conceptual approaches, examining relevant laws, regulations, and construction contract practices. The findings reveal that administrative responsibility in construction contracts tends to be asymmetric, with service providers bearing disproportionate risks and sanctions compared to service users. This imbalance is reflected in mechanisms such as fines, variation order authority, force majeure procedures, unilateral contract termination, licensing burdens, and the application of administrative sanctions. These conditions increase financial and administrative risks for service providers, weaken the integrity of administrative law, and create potential disputes in the construction sector. Therefore, strengthening the principle of balanced administrative responsibility is essential to ensure justice, legal certainty, and sustainable development in the national construction industry.